Frequency of medical evaluations for peripheral vestibular dysfunction in hospitals level III, Peru - Tapia-Egoavil, Raquel (2019)
Peripheral vestibular dysfunction produces a vestibular syndrome that affects routine daily activities leading to incapacity and impacting negatively on quality of life. The prevalence of this condition is high and increases with age, and it consumes significant resources due to the relapsing nature of the condition rising the burden of disease. Objective: To determine the frequency of medical evaluations for peripheral vestibular dysfunction by diagnosis, age, gender and by the specialty offering the medical evaluation. Methods: A descriptive and observational study was carried out including hospitals level III ruled by the Ministry of Health (MOH) at a national scale, data were gathered from the MOH database over a period of 3 years. Results: A total of 18 349 medical evaluations were analyzed; 68% of them occurred in females and were offered by neurologist and otorhinolaryngologists. The most common diagnoses were non-specified vertiginous syndrome 46.10%, other peripheral vertigo 18.58% and benign paroxysmal vertigo 16.91%. Conclusions: Most of the medical evaluation occurred in women by otorhinolaryngologists, the most common diagnosis was non-specified vertiginous syndrome. This information may allow to plan an adequate sanitary response.